Entrepreneurial Value Development Strategy in Early Childhood through Outingclass Activities at the Leading Islamic Kindergarten Al-Khoir Boyolali - Aljawad, Havida Inaya; Widyasari, Choiriyah (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study analyzes strategies for instilling entrepreneurial values in early childhood through outing class activities at Al‑Khoir Kindergarten Boyolali. In response to globalization’s increasing competitiveness, the research seeks to determine how real‑world experiences can prepare young learners to face future challenges with creativity, independence, and problem‑solving skills. Methodology: A qualitative approach was employed, utilizing direct observation of outing class sessions, semi‑structured interviews with teachers, parents, and community partners, and review of program documentation. Observations focused on children’s engagement during visits to business premises, traditional markets, and agricultural sites, while interviews explored stakeholders’ roles in designing and facilitating these thematic learning experiences. Results: Findings reveal that outing class programs—tailored to children’s developmental stages—effectively embed entrepreneurial values by allowing youngsters to observe and interact with real entrepreneurs. Collaborative planning between teachers, parents, and local businesses enriched the activities, fostering children’s creativity, autonomy, and emerging problem‑solving abilities. Key challenges included limited scheduling flexibility, resource constraints, and the need to continuously adapt materials to suit varying developmental levels. Applications/Originality/Value: By demonstrating that hands‑on, community‑linked outings can build foundational entrepreneurial mindsets, this study offers a replicable model for early‑childhood centers seeking to expand beyond classroom walls. Its insights highlight the importance of multi‑stakeholder collaboration and age‑appropriate program design, informing policymakers, educators, and parent groups on how to strengthen support systems and optimize the impact of entrepreneurial learning from a young age.